On a graph isomorphic to its intersection graph: self-graphoidal graphs - Das, P.K.; Singh, K.R. (Algebra and Discrete Mathematics, 2018)
A graph G is called a graphoidal graph if there exists a graph H and a graphoidal cover ψ of H such that G ≅ Ω (H, ψ ). Then the graph G is said to be self-graphoidal if it is isomorphic to one of its graphoidal graphs. In this paper, we have examined the existence of a few self-graphoidal graphs from path length sequence of a graphoidal cover and obtained new results on self-graphoidal graphs.